Evaluasi Konservasi Bangunan Candra Naya di Jakarta Farah Athaya Salsabilani - Farah Athaya Salsabilani (Jurnal Mahasiswa Jurusan Arsitektur, 2022)
Candra Naya is one of a Chinese architectural building that has been standing since the 19th century. During its journey, this building has undergone several conversions from being a residence to now becoming a museum. After being conserved with the adaptive re-use into a museum and the construction of new buildings around it, many adjustments were made to the Candra Naya building. This study was conducted to assess the authenticity of the post-conservation Candra Naya. This research was conducted using an exploratory mixed method, identify as combination of qualitative and quantitative. The evaluation results indicate that the authenticity of the Candra Naya building is in the proper category. The building elements, both visually, spatially and structurally, are still in accordance with the original, some materials are only polished for maintenance. Some of the changes made to the building are non-destructive and only as an adjustment to the new building built on the site.